Heat treatment of cold-sprayed C355 Al for repair: microstructure and mechanical properties - Murray, J.W.; Zuccoli, M.V.; Hussain, Tanvir (Springer, 2017)
Cold gas dynamic spraying of commercially pure aluminum is widely used for dimensional repair in the aerospace sector as it is capable of producing oxide-free deposits of hundreds of micrometer thickness with strong bonding to the substrate, based on adhesive pull-off tests, and often with enhanced hardness compared to the powder prior to spraying. There is significant interest in extending this application to structural, load-bearing repairs. Particularly, in the case of high-strength aluminum alloys, cold spray deposits can exhibit high levels of porosity and microcracks, leading to mechanical properties that are inadequate for most load-bearing applications. Here, heat treatment was investigated as a potential means of improving the properties of cold-sprayed coatings from Al alloy C355. Coatings produced with process conditions of 500 °C and 60 bar were heat-treated at 175, 200, 225, 250 °C for 4 h in air, and the evolution of the microstructure and microhardness was analyzed. Heat treatment at 225 and 250 °C revealed a decreased porosity (~ 0.14% and 0.02%, respectively) with the former yielding slightly reduced hardness (105 versus 130 HV0.05 as-sprayed). Compressive residual stress levels were approximately halved at all depths into the coating after heat treatment, and tensile testing showed an improvement in ductility.